Kinetic study of the pyrolysis of microalgae under nitrogen and CO2 atmosphere - Hong, Yu; Xie, Chengrui; Chen, Wanru; Luo, Xiang; Shi, Kaiqi; Wu, Tao (Elsevier, 2020)
In this study, three primary components of algae (lipid, carbohydrate and protein) and one microalgae (spirulina) were pyrolyzed using a thermogravimetric analyser (TGA) under nitrogen and CO2 atmosphere at four heating rates. It was found that protein decomposed first, followed by carbohydrate and then lipid. The kinetic study revealed that the lowest activation energy for the initiation of the pyrolysis of ovalbumin (protein) is ∼70 kJ/mol. Oil droplet showed higher activation energy of 266.5 kJ/mol during its pyrolysis in the CO2 atmosphere, which suggests that algal lipid is more difficult to decompose in the CO2 atmosphere. However, for the pyrolysis of cellulose (carbohydrate), the activation energy (∼310 kJ/mol) is similar under two different gas atmospheres tested. This study showed that CO2 atmosphere favors the pyrolysis of algae with high protein content and low lipid content, since the existence of CO2 promotes the cracking of VOCs (volatile organic compounds) as well as the reaction between VOCs and CO2.